A requirement model for managing inventory of raw materials - Hashim, Nor Laily; Mohd Ghouse, Nor Zahirah; Ismail, Noraini (2012)
This study presents an initial study on managing knowledge related to consumption of raw food inventory used in an organization that deals with preparing food and beverage services. A requirement model capturing the functionalities of this system is proposed, where its prototype has been evaluated using TAM.The finding from this evaluation shows that this prototype is easy to use and provide useful function to its target users.